A parametric investigation of the influence of atrium facades on the daylight performance of atrium buildings - Samant, Swinal R. (2011)
Atria have proliferated in a range of contemporary buildings and daylighting is perhaps their most valuable aspect. This thesis is an exploration of the effects of atrium facades on the daylight performance of an atrium and its adjoining spaces. It examines the effects of atrium wall surface reflectance distribution patterns, different surface types, and the location, size and proportion of fenestration and opaque areas in an atrium’s facade. The study seeks to provide knowledge that would be most useful at the early design stages of a project.